Metalloproteinases and Advanced Glycation End Products: Coupled Navigation in Atherosclerotic Plaque Pathophysiology? - Furfaro, A. L.; Sanguineti, R.; Storace, D.; Monacelli, F.; Puzzo, A.; Pronzato, M. A.; Odetti, P.; Traverso, N. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Matrix metalloproteinases (MMPs), their inhibitors (TIMPs) and inflammatory cytokines, such as interleukin-1 (IL-1), are considered markers of evolution and/or instability of atherosclerotic plaques. Accumulation of Advanced Glycation Endproducts (AGE) is a well known phenomenon in diabetes and has also been considered in the pathogenesis of atherosclerosis. Aim of the present study was to analyse the levels of pentosidine, a fluorescent AGE, and to evaluate the expression of MMP-2, TIMP-3, and IL-1 in an ex vivo model of human advanced atherosclerotic plaques. We intended to test the possible correlation between pentosidine and markers of ECM remodelling and inflammation in the atherosclerotic process, and to investigate if classic risk factors, such as diabetes and hypertension, influenced these biochemical parameters. We found that diabetic plaques showed higher level of pentosidine, as expected, but much lower, or even undetectable, expression levels of MMP-2 and TIMP-3; IL-1 expression was not different between diabetic and non diabetic plaques. Hypertension did not influence any of these parameters. Although the statistical correlations between the expression of the considered genes and pentosidine did not reach significance, slight negative trends were noted between TIMP-3 and IL-1 expression vs. pentosidine content. We suggest that in mature diabetic plaques AGE accumulation can exert stabilizing effects on matrix proteins, while scanty cell presence leads to poor capacity of reactive responses, such as remodelling and inflammation.
Keywords: diabetes; atherosclerosis; pentosidine; MMP-2; TIMP-3; IL-1